PRELIMINARY STATUS OF NATIVE EARTHWORMS IN JOTSOMA VILLAGE OF KOHIMA DISTRICT - LILONGCHEM THYUG; PELESANO KIN; RUOKUOVIKHO DOMINIC RUSOKHRIENUO THEUNUO (The Bioscan, 2024)
The present study was carried out to examine the distribution of native earthworms around Jotsoma village , Kohima. The survey was performed from September 2021-April 2022 in four study Sites viz Grassland, Vegetable garden, Reserved Forest and Residential area. Soil temperature and pH of the soil were recorded from the sampling sites. Based on their habitat and important morphological characters such as colour, length, presence of the clitellum and their behaviour, five genera and three families of earthworms were represented among 9 species found at the study sites.The three families recorded were; Megascolecidae, Moniligastridae and Octochaetidae. Among the 9 species, 7 species were classified under the family Megascolecidae and a single species each represented family Moniligastridae and Octochaetidae respectively. This study showed that Family Megascolecidae was more abundant amongst the three recorded families. The species recorded were: Perionyx excavatus, Perionyx sp. 1, Perionyx sp. 2, Metaphire houlleti, Metaphire sp. 1, Amynthas corticis, Amynthas sp. 1, Drawida sp. and Eutyphoeus sp. Genus Perionyx was found to be the dominant species while genus Drawida and Eutyphoeus exhibited the least count.